Optimization of synthesis conditions of hydrochar and pyrohydrochar from fish bones for their use in the adsorption of fluoride from water - Sergio Armando Cruz Briano; Nahum Andrés Medellín Castillo; Juan Carlos Moreno Piraján; Liliana Giraldo Gutiérrez; Guillermo Javier Castro Larragoitia; Pablo Delgado Sánchez; Alfredo Israel Flores Rojas; Hilda Guadalupe Cisneros Ontiveros (Sustainable Chemistry for the Environment, 2024)
In this study, the optimization of the synthesis variables of hydrochar (HC) and pyrohydrochar (PHC) obtained from pleco fish spines that would generate the highest fluoride adsorption capacity and synthesis yield was carried out. For this purpose, a D-Optimal experimental composite central design was established using response surface methodology (RSM) considering three levels for temperature and synthesis time. Hydrochar was produced by hydrothermal carbonization at temperatures of 180–240 °C for 4–8 h in the presence of water under autogenous pressure. On the other hand, pyrohydrochar was obtained by pyrolysis of hydrochar in the absence of water at temperatures of 350–650 °C for 1–2 h at autogenous pressures (2–20 MPa). The results of the D-Optimal design indicated that the materials synthesized at lower temperatures and times, particularly at 180 °C - 4 h (HC1) and 350 °C - 1.5 h (PHC5), achieved the highest adsorption yield and capacity, with values of 87.9 % and 5.27 mg g−1; and 94.8 % and 5.73 mg g−1 for HC1 and PHC5, respectively. Analysis of variance (ANOVA) on the synthesis model revealed that temperature and carbonization time are significant factors, both factors have an influence on HC and PHC fluoride adsorption capacity and HC yield and only temperature affects PHC yield. The optimum synthesis conditions to obtain the highest yields were 180 °C for 4 h and 350 °C for 1 h for HC and PHC, respectively, with 88.4 % and 96.2 % values. As for the maximum adsorption capacity, the optimum temperature and time values were 185 °C for 4 h and 378 °C for 1 h for HC and PHC, respectively, reaching adsorption capacities of 5.27 mg g−1 and 5.64 mg g−1. In addition, HC1 and PHC5 materials were characterized by N2 physisorption, Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), CHNS elemental analysis and scanning electron microscopy (SEM). These materials showed differences among themselves, where the higher specific area of PCH5 with 137 m2 g−1, with respect to HC1 with 119 m2 g−1, stands out, as well as a higher concentration of basic sites, being 1.65 and 1.40 meq g−1 for HC1 and PHC5, respectively, on the other hand, the FTIR showed the same functional groups present on the surface, although in the SEM it was observed that the surface of HC1 presented small fractures, which disappeared when subjected to the pyrolysis process, in addition, the TGA showed a greater amount of organic matter in HC1 that could affect the adsorption of fluorides. The effect of pH on the adsorption capacity of HC1 and PHC5 fluorides was also investigated, revealing an increase of this capacity with decreasing solution pH due to electrostatic forces.